2008
DOI: 10.3989/gya.2008.v59.i1.490
|View full text |Cite
|
Sign up to set email alerts
|

Pistachio (<i>Pistacia vera</i>) seed oil composition: geographic situation and variety effects

Abstract: Composición del aceite de la semilla del pistacho (Pistacia vera): efectos de la situación geográfica y de la variedad. Este estudio tiene como objetivo caracterizar cuatro cultivos de pistacho (Pistacia vera) de Túnez, de las regiones de Mateur (Norte), Nabeul (Nordeste), Kairouan (Centro) y Sfax (Centro-Este) y dos variedades, Mateur and Ohadi, considerando la composición en ácidos grasos y de lípidos mayoritarios (lípidos polares, diglicéridos, triglicéridos y ácidos grasos libres) de semillas maduras. Los … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 20 publications
3
17
1
1
Order By: Relevance
“…In our work, the examined pistachios had a greater quantity of oleic acid compared to the work of Tsantili et al 2010 that found a percentage of 60.4%. Important differences were noted between fatty acids ratio of Turkish (Satil et al 2003;Ozrenk et al 2012), Tunisian (Chahed et al 2008), Iranian pistachios (Okay 2002) and what was found in our study. Satil et al 2003 revealed oleic acid contents much lower than our study, with minimum of 55.4% and maximum of 62.6%.…”
Section: Resultscontrasting
confidence: 57%
“…In our work, the examined pistachios had a greater quantity of oleic acid compared to the work of Tsantili et al 2010 that found a percentage of 60.4%. Important differences were noted between fatty acids ratio of Turkish (Satil et al 2003;Ozrenk et al 2012), Tunisian (Chahed et al 2008), Iranian pistachios (Okay 2002) and what was found in our study. Satil et al 2003 revealed oleic acid contents much lower than our study, with minimum of 55.4% and maximum of 62.6%.…”
Section: Resultscontrasting
confidence: 57%
“…In fact, they account for more than 90% of the total glycerolipids content (Chahed et al 2008). The TGs of pistachio oil have been separated by HPLC according to their degree of unsaturation and their total number of carbon atoms in the three fatty acyl chains (Holcapek et al 2003;Ballistreri et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Triacylglycerols (TGs) constitute the main acylglycerols in pistachio oil (more than 90% of the total glycerolipids) (Chahed et al 2008). The TGs of pistachio are rich in polyunsaturated fatty acids such as linoleic and linolenic acids, essentials for human diet, and monounsaturated fatty acids such as oleic acid (Anderson & Smith 2005;Arena et al 2007;Ballistreri et al 2010).…”
mentioning
confidence: 99%
“…Chemical studies on pistachio kernels mainly regarded the fatty acids and sterols content (Arena, Campisi, Fallico, & Maccarone, 2007;Chahed et al, 2006;Chahed et al, 2008;Daneshared & Aynehchi, 1980;Okay, 2002;Phillips, Ruggio, & Ashraf-Khorassani, 2005;Ryan, Galvin, O'Connor, Maguire, & O'Brien, 2006;Satil, Azcan, & Baser, 2003;Venkatachalam & Sathe, 2006;Yildiz, Turcan Gurcan, & Ozdemir, 1998); other studies concern the kernel pigments characterisation (Bellomo & Fallico, 2007;Giuffrida, Saitta, La Torre, Bombaci, & Dugo, 2006;Wu & Prior, 2005), the resveratrol recovery in seeds (Gentile et al, 2007;Grippi et al, 2008;Tokusoglu, Unal, & Yemis, 2005) and the presence of anacardic acids in the outer green shell (Yalpani & Tyman, 1983).…”
Section: Introductionmentioning
confidence: 99%